Case Report: Indwelling Pleural Catheter Based Management of Refractory Hepatic Hydrothorax as a Bridge to Liver Transplantation - Selvan, Mayurun; Collins, Hannah; Griffiths, William; Gelson, William; Herre, Jurgen (Frontiers in Medicine, 2021)
Introduction: Liver transplantation is the treatment of choice for decompensated liver disease, and by extension for hepatic hydrothorax. Persistent pleural effusions make it challenging for patients to maintain physiological fitness for transplantation. Indwelling pleural catheters (IPCs) provide controlled pleural fluid removal, including peri-operatively. The immune dysfunction of cirrhosis heightens susceptibility to bacterial infection and concerns exist regarding the sepsis potential from a tunnelled drain. Method: Six patients were identified who underwent IPC insertion for hepatic hydrothorax before successful liver transplantation, between November 2016 and November 2017. Results: All patients had recurrent transudative right sided pleural effusions. Mean age was 49 years (range 24-64) and mean United Kingdom Model for End-Stage Liver Disease score was 58. Four patients required correction of coagulopathy before insertion. There were no complications secondary to bleeding. Three patients were taught self-drainage at home of up to 1 litre (L) daily. A protocol was developed to ensure weekly review, pleural fluid culture and drainage of larger volumes in hospital. For every 2-3L of pleural fluid drained, 100mls of 20% Human Albumin Solution (HAS) was administered. On average an IPC was in situ for 58 days before surgery and drained 19L of fluid in hospital. There was a small increase in average BMI (0.2) and serum albumin (2.1g/L) at transplantation. There was one episode of stage one acute kidney injury secondary to high volume drainage. No further ascitic or pleural procedures were needed while an IPC was in situ. One thoracentesis was required after IPC removal. On average IPCs remained in situ for 7 days post transplantation and drained a further 2L of fluid. Pleural fluid sampling was acquired on 92% of drainages in hospital. Of 44 fluid cultures, 2 cultured bacteria. Two patients had their IPCs and all other lines removed post transplantation due to suspected infection. Conclusion: Our case series describes a novel protocol and successful use of IPCs in the management of refractory hepatic hydrothorax as a bridge to liver transplantation. The protocol includes albumin replacement during pleural drainage, regular clinical review and culture of pleural fluid, with the option of self-drainage at home.